Problems of conceptualization of administrative and legal regulation in the healthcare sector of the Republic of Kazakhstan - Bogatyreva, L.B.; Taitorina, B.A.; Satbayeva, A.M. (Bulletin of the Karaganda University “Law Series”, 2023)
The study analyzed social relations in the field of medical activity, problems of their legal regulation during various periods of formation of these relations. The subject of the study is the source and regulatory frame work of health care of the Republic of Kazakhstan. The study of the problem was carried out on the basis of an analysis of the historical retrospective of the development of medical law in Kazakhstan from 1913 to the present day, there was given a description and assessment of the main trends in the development of medical law, determined prospects for the development of this branch of law. Based on the study of the phenomenon of health care, the generalization of the theory and practice of international legal and state-legal impact on public relations in the field of health care, an attempt was made to identify and conceptually substantiate the legal foundations for the organization and implementation of legal regulation of the health care system in the Republic of Kazakhstan. The article formulates provisions that develop modern ideas about the essence of legal regulation of the health care system. Special attention is paid to the study of the general and political and legal aspects of the formation and development of the health care system, its place and role in the life of society and functional manifestations in the real state-legal reality of the Republic of Kazakhstan. Modern ideas about the problems of public health management are based on the need to solve the problem of improving the state’s capacity in the field of public health.